Private Power Projects : Annual Investment Flows Grew by 44 Percent in 2003 - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Drawing on the Bank's Private Participation in Infrastructure Project Database, this Note reviews developments in the electricity sector in 2003. Data for the year show that total investment in electricity projects with private participation amounted to US$14 billion. Private activity grew strongly in East Asia and Pacific, but remained stable, or fell in other regions. After the boom of 1996-2000, investment flows to electricity fell significantly after peaking in 1997, but are still comparable to pre-boom levels. Annual investment flows in 2001-03 averaged US$12.9 billion, slightly higher than the US$12.2 billion in 1990-95. During the boom of 1996-2000 annual flows averaged US$29.8 billion. The decline in private activity played out differently across the developing regions. Latin America, the most active region in the late 1990s, sustained investment flows at levels higher than those of the early 1990s, while East and South Asia saw annual flows fall below those levels